Relasi Ilmu, Kuasa Dan Kepentingan Dalam Potret Kebijakan Sains Di Indonesia Perspektif Triple Helix - Etzkowitz - Gede Agus Siswadi; Galuh Nur Fattah (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2022)
The debate between value-free science and value-anchored science is a discourse which at this time has not found a definite conclusion. On the one hand, scientists demand that science always be developed based on science alone and should not be developed on the basis of other considerations outside of science. Of course, this demand is based on the premise that science does not distort or submit to other sciences and ultimately science can develop autonomously. But on the other hand, science has a tendency that cannot be free from values. Science is always filled with strong values and pragmatists. Science, like it or not, always cares about the problems of human suffering, science also cares about human safety as well as cares about human dignity. In this case, it is very clear that science as a complex structure in the sense that science always has the dimension of influencing and being influenced between science and social culture, education, ideology or politics, economy and religion. By using the phenomenological approach and the Triple Helix theory from Etzkowitz, it can be understood that the portrait of science policy in Indonesia is also colored by power and interest. The development of science in Indonesia is a synergy of three interrelated elements, namely the nation state, academia and industry. The relationship of mutual influence and influence from these three aspects is a form of representation of ideology, namely the ideology of Pancasila, science (academics/scientists) and also economics.